1975
DOI: 10.1016/0041-3879(75)90065-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term beclomethasone dipropionate aerosol therapy in juvenile asthma

Abstract: Long-term beclomethasone dipropionate aerosol therapy in juvenile asthma. Following a short-term clinical trial reported elsewhere, beclomethasone dipropionate aerosol has been given to 15 children with asthma for between 21 and 3 years except for a short placebo period after the first year. Month-bymonth records of wheezing, peak flow rate, and other treatments used are presented for the first 17 months, adrenocortical function tests are reported for the first 2 years, and growth is recorded for 24-3 years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 1 publication
(1 reference statement)
0
12
0
Order By: Relevance
“…The direct influence of asthma on growth makes it difficult to assess the effects of corticosteroids in crosssectional studies, although the majority of these studies have shown no effect of inhaled corticosteroids [67][68][69][70][71][72][73][74][75][76]. Longitudinal studies have also generally failed to demonstrate any significant effect of inhaled corticosteroids on statural growth in doses up to 800 µg·day -1 for up to 5 yrs of treatment [62,[77][78][79].…”
Section: Effect Of Corticosteroids On Growthmentioning
confidence: 99%
“…The direct influence of asthma on growth makes it difficult to assess the effects of corticosteroids in crosssectional studies, although the majority of these studies have shown no effect of inhaled corticosteroids [67][68][69][70][71][72][73][74][75][76]. Longitudinal studies have also generally failed to demonstrate any significant effect of inhaled corticosteroids on statural growth in doses up to 800 µg·day -1 for up to 5 yrs of treatment [62,[77][78][79].…”
Section: Effect Of Corticosteroids On Growthmentioning
confidence: 99%
“…'0 11 The effect of ICT on linear growth, is however, controversial. 3 [12][13][14] This study evaluated the effects of ICT and the severity of asthma on linear growth in prepubertal children with severe chronic bronchial asthma, many of whom were poorly controlled despite higher than conventionally recommended doses of ICT.…”
mentioning
confidence: 99%
“…Some of the children in the studies had received oral glucocorticosteroids until the inhaled therapy was introduced [50][51][52][53][54], and continued to do so intermittently [50,53]. In the study by TINKELMAN et al [58], the beclomethasone dipropionate-treated children were compared with theophylline-treated children, who grew somewhat faster than expected during the study period.…”
Section: Intermediate-term Growthmentioning
confidence: 99%
“…In the studies of beclomethasone dipropionate, the dose often varied and, in one study [51], the treatment was withdrawn for some months during the observation period. Some of the children in the studies had received oral glucocorticosteroids until the inhaled therapy was introduced [50][51][52][53][54], and continued to do so intermittently [50,53].…”
Section: Intermediate-term Growthmentioning
confidence: 99%
See 1 more Smart Citation